ANALISIS KESULITAN KEUANGAN PT SRITEX - Ramdani, Edon (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the financial performance of PT Sritex in the period 2014 to 2024, so that it was declared bankrupt in 2025. What factors caused the Company to go bankrupt. measurement of financial difficulties using the Grover, Springate and Zmijewski models. The three models are used because they are common or frequently used and the measurement method is simple but is able to provide a fairly strong picture of the potential bankruptcy of a Company. Based on the calculation of financial difficulties with three models namely Grover, Springate and Zmijewski, the three models produce the same conclusion that PT Sritex has been in financial difficulties from 2021 to 2024. Financial difficulties began in 2021 where the Company's working capital was in a minus position of 982,037,149 US , although in terms of sales it was still quite high at 847,523,131 US but the Company's profits were unable to cover the debt which had reached 1,571,358,369 US . In the case of PT Sritex, it can be concluded that the financial difficulties experienced by the Company were caused by two main factors, namely, a very large increase in the amount of debt in 2021 without being accompanied by the ability of the Company's management to earn sufficient profits to pay the Company's obligations, then another main factor is poor Corporate Governance, where debt that should have been used to increase the Company's productivity was actually misused by the Company's management. Keywords: Performance, Finance, Bankruptcy, Sritex, Governance